Oral collagen supplementation and its effects on skin (Research, Society and Development, 2023)
Aging process negatively affects skin due to changes in the proteins that make up its connective tissues, more specifically collagen, the main goal of this study. This work consists of a literature review with a qualitative approach. Pubmed, Medline, LILACS, Scielo and Scholar Google databases were used database. Studies have shown that collagen is absorbed through the intestine, is distributed in tissues and stimulates fibroblast activity. Beneficial effects were observed on the aesthetic and functional quality of the skin related to the nutraceutical intake; no associated complications are known.